2022
DOI: 10.3389/fonc.2022.981226
|View full text |Cite
|
Sign up to set email alerts
|

Histone lysine methylation patterns in prostate cancer microenvironment infiltration: Integrated bioinformatic analysis and histological validation

Abstract: BackgroundEpigenetic reprogramming through dysregulated histone lysine methylation (HLM) plays a crucial role in prostate cancer (PCa) progression. This study aimed to comprehensively evaluate HLM modification patterns in PCa microenvironment infiltration.Materials and methodsNinety-one HLM regulators in The Cancer Genome Atlas (TCGA) dataset were analyzed using bioinformatics. Differentially expressed genes (DEGs) and survival analyses were performed using TCGA-PRAD clinicopathologic and follow-up information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…203 Similar results of histone lysine methylation (HLM) regulators ((EZH2, NSD2, and KMT5C) found in an analysis of The Cancer Genome Atlas (TCGA)-PRAD dataset. 204 Another study also observed a strong connection between EZH2 expression and macrophage infiltration in breast cancer, suggesting that modulating epigenetic regulation to control macrophage activation is a potential therapeutic strategy for breast cancer. 205 The role of total histone H4 methylation (H4M) modification in the TME and immune regulation in HCC has also been recently reported.…”
Section: Histone Modificationmentioning
confidence: 96%
“…203 Similar results of histone lysine methylation (HLM) regulators ((EZH2, NSD2, and KMT5C) found in an analysis of The Cancer Genome Atlas (TCGA)-PRAD dataset. 204 Another study also observed a strong connection between EZH2 expression and macrophage infiltration in breast cancer, suggesting that modulating epigenetic regulation to control macrophage activation is a potential therapeutic strategy for breast cancer. 205 The role of total histone H4 methylation (H4M) modification in the TME and immune regulation in HCC has also been recently reported.…”
Section: Histone Modificationmentioning
confidence: 96%